2015
DOI: 10.1111/ecc.12423
|View full text |Cite
|
Sign up to set email alerts
|

The impact of new generic formulations of imatinib mesylate on general quality of life in chronic phase chronic myeloid leukaemia patients

Abstract: Treatment with tyrosine kinase inhibitors (TKIs) has dramatically changed the life expectancy of chronic myeloid leukaemia (CML) patients. Although the impact of first-generation TKIs on quality of life (QoL) was shown in CML, the effects of new generic formulations of imatinib mesylate (IM) are unclear. We evaluated differences in QoL under treatment with first- or second-generation TKIs. Fifty-two patients diagnosed with CP-CML completed the European Organization for Research and Treatment of Cancer Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Uyanik MS et al [12], Klil-Drori AJ et al [13] ont montré une aggravation des effets secondaires après le passage de la molécule d'origine au générique. Chez les patients initialement mis sous générique, Abdalla Awidi et al ont montré que 89 % ont eu des effets secondaires dont 13,5 % sont de grade 3 et 4 [14].…”
Section: Page14unclassified
See 1 more Smart Citation
“…Uyanik MS et al [12], Klil-Drori AJ et al [13] ont montré une aggravation des effets secondaires après le passage de la molécule d'origine au générique. Chez les patients initialement mis sous générique, Abdalla Awidi et al ont montré que 89 % ont eu des effets secondaires dont 13,5 % sont de grade 3 et 4 [14].…”
Section: Page14unclassified
“…Generic Imatinib Mesylate as first line treatment of chronic myeloid leukemia. Batna J Med Sci 2023;10(1):[12][13][14][15][16]…”
mentioning
confidence: 99%
“…Two additional studies showed significantly worsening toxicities under generics emerging after switching from the original molecule. 38,39 Most of these AEs were nausea, diarrhea, edema, muscle cramps, and fatigue, but only a couple of patients switched back to branded imatinib because of gastrointestinal toxicities in both studies. On the other hand, a recently published study displayed significantly improved muscle cramps, edema, fatigue, and diarrhea after switching to generics.…”
Section: Efficacy and Safety Of Generic Imatinibmentioning
confidence: 99%